Surveillance of physical activity in the UK is flawed: validation of the Health Survey for England Physical Activity Questionnaire. Issue 12 (9th September 2008) - Basterfield, L; Adamson, A J; Parkinson, K N; Maute, U; Li, P X; Reilly, J J; ,
Abstract : Objective: Public health surveillance of physical activity in children in the UK depends on a parent-reported physical activity questionnaire which has not been validated. We aimed to validate this questionnaire against measurement of physical activity using accelerometry in 6–7-year-old children. Methods: In 130 children aged 6–7 years (64 boys, 66 girls) we estimated habitual moderate–vigorous intensity physical activity (MVPA) using the Health Survey for England parent-report questionnaire for physical activity. For the same time period and the same children, we measured MVPA objectively using 7-day accelerometry with the Actigraph accelerometer. Results: The questionnaire over-estimated MVPA significantly (paired t test, p<0.01). Mean error (bias) when using the questionnaire was 122 min/day (95% CI 124 to 169). Mean time spent in MVPA was 146 min/day (95% CI 124 to 169) using the questionnaire and 24 min/day (95% CI 22 to 26) using the accelerometer. Rank order correlations between MVPA measured by accelerometer and estimated by the questionnaire were not statistically significant. Conclusions: Public health surveillance of physical activity should not rely on this questionnaire. Levels of habitual physical activity in children are likely to be substantially lower than those reported in UK health surveys.